Cefiderocol in Combating Carbapenem-Resistant Acinetobacter baumannii: Action and Resistance - Bahman Yousefi; Setayesh Kashanipoor; Payman Mazaheri; Farnaz Alibabaei; Ali Babaeizad; Shima Asli; Sina Mohammadi; Amir Hosein Gorgin; Tahereh Alipour; Valentyn Oksenych; Majid Eslami (Biomedicines)
Acinetobacter baumannii (A. baumannii) has emerged as a prominent multidrug-resistant (MDR) pathogen, significantly complicating treatment strategies due to its formidable resistance mechanisms, particularly against carbapenems. Reduced membrane permeability, active antibiotic efflux, and enzymatic hydrolysis via different β-lactamases are the main resistance mechanisms displayed by A. baumannii, and they are all effective against successful treatment approaches. This means that alternate treatment approaches, such as combination therapy that incorporates beta-lactams, β-lactamase inhibitors, and novel antibiotics like cefiderocol, must be investigated immediately. Cefiderocol, a new catechol-substituted siderophore cephalosporin, improves antibacterial activity by allowing for better bacterial membrane penetration. Due to its unique structure, cefiderocol can more efficiently target and destroy resistant bacteria by using iron transport systems. Through its inhibition of peptidoglycan formation through binding to penicillin-binding proteins (PBPs), cefiderocol avoids conventional resistance pathways and induces bacterial cell lysis. The possibility of resistance development due to β-lactamase synthesis and mutations in PBPs, however, emphasizes the need for continued investigation into cefiderocol’s efficacy in combination treatment regimes. Cefiderocol’s siderophore mimic mechanism is especially important in iron-limited conditions because it can use ferric-siderophore transporters to enter cells. Additionally, its passive diffusion through bacterial porins increases its intracellular concentrations, making it a good option for treating carbapenem-resistant A. baumannii, especially in cases of severe infections and ventilator-associated diseases (IVACs). Cefiderocol may reduce MDR infection morbidity and mortality when combined with customized antimicrobial treatments, but further investigation is needed to improve patient outcomes and address A. baumannii resistance issues.